Structure and modes of dc glow discharge in nitrogen with hollow cathode or anode - Lisovskiy, V.A.; Osmayev, R.O.; Khilko, D.I.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2018)
This paper studies the modes of burning and structure of the glow discharge with "hollow cathode and flat anode" and "hollow anode and flat cathode" in nitrogen. We have demonstrated that a higher discharge current is observed with a hollow cathode because its area exceeds 3 times that of a flat one. The discharge with a hollow cathode may burn in hollow or glow modes (with the cathode cavity filled with negative glow or not). We have measured the axial profiles of the emission line intensities for nitrogen molecules, atoms and ions with different gas pressure, discharge current values and electrode designs. We have observed the high intensity of the emission lines of
the atomic nitrogen in the cathode sheath near the surface of the flat cathode indicating a remarkable dissociation
degree of nitrogen molecules in this region of the discharge. Досліджені режими горіння і структура тліючого розряду з «порожнистим катодом і плоским анодом» і
«порожнистим анодом і плоским катодом» в азоті. Показано, що більш високий розрядний струм спостерігається для порожнистого катоду, оскільки його площа в 3 рази більша, ніж плоского. Розряд з порожнистим
катодом може горіти в порожнистому або тліючому режимах (з катодною порожниною, заповненою негативним світінням чи ні). Для різних значень тиску газу, розрядних струмів і геометрій електродів побудовані
осьові профілі інтенсивності ліній випромінювання молекул, атомів та іонів азоту. Поблизу поверхні плоского катоду в катодному шарі спостерігається висока інтенсивність ліній випромінювання атомарного азоту,
що вказує на значний ступінь дисоціації молекул азоту в цій області розряду. Исследованы режимы горения и структура тлеющего разряда с «полым катодом и плоским анодом» и
«полым анодом и плоским катодом» в азоте. Показано, что более высокий разрядный ток наблюдается для
полого катода, так как его площадь в 3 раза больше, чем плоского. Разряд с полым катодом может гореть в
полом или тлеющем режимах (с катодной полостью, заполненной отрицательным свечением или нет). Для
различных давлений газа, разрядных токов и геометрий электродов построены осевые профили интенсивности линий излучения молекул, атомов и ионов азота. Вблизи поверхности плоского катода в катодном слое
наблюдается высокая интенсивность линий излучения атомарного азота, что указывает на значительную
степень диссоциации молекул азота в этой области разряда.